OS 34-01 ASSOCIATION OF COMBINATION OF HYPERTENSION AND DIABETES WITH COGNITIVE FUNCTION AMONG THE 70-YEARS-OLD JAPANESE GENERAL POPULATION FROM LONGITUDINAL OBSERVATION IN THE SONIC STUDY. (September 2016) - Ryuno, Hirochika; Kamide, Kei; Gondo, Yasuyuki; Kabayama, Mai; Sugimoto, Ken; Nakagawa, Takeshi; Ikebe, Kazunori; Inagaki, Hiroki; Masui, Yukie; Arai, Yasumichi; Ishizaki, Tatsuro; Rakugi, Hiromi
Abstract : Objective: It is well-documented that midlife hypertension (HT) is associated with decline of cognitive function. Recently, we reported that the influence of HT and/or elevated blood pressure on the progression of cognitive decline was attenuated at late life aged 70 of the general population in cross-sectional analysis. The purpose of this study is to investigate the 3 years' longitudinal effect of HT and additive risk factors on decline of cognitive function for 70-year-old general Japanese population in the Septuagenarians, Octogenarians and Nonagenarians Investigation with Centenarians (SONIC) study, which is a narrow age range cohort. Design and Method: Six hundred thirty-two subjects age 70 ± 1 (49.7% men) who participated in SONIC were randomly recruited from general population and performed the follow-up study after 3 years. Data abstracted included demographics, cognitive function measured by Montreal Cognitive Assessment Japanese version (MoCA-J), blood pressure, blood sample, and other medical history. Multiple linear regression models were produced to calculate the standardized regression coefficients expressing independent statistical associations between variables. Results: After 3 years' follow-up, proportion of HT, diabetes mellitus (DM) and dyslipidemia (72.2%, 19.1% and 72.1%, respectively) were significantly higher than those at baseline (65.8%, 18.8% and 64.1%, respectively), whereas, systolic and diastolic blood pressure at follow-up period were significantly lower than those at baseline. MoCA-J score at follow-up was not significantly different from baseline, however, peoples with HT, especially combined with DM at baseline were significantly lower MoCA-J scores at follow-up (−0.6 and −1.4, respectively). Additionally, combination of HT and DM was the significant risk factor for the decline of MoCA-J scores after adjustment for sex, BMI, dyslipidemia, smoking, excessive alcohol intake, and education level (β = −0.12; p < 0.05). Conclusions: Our findings from the longitudinal study indicate that HT, especially combination of HT and DM is the risk factor of cognitive decline at late life aged around 70.